2020
DOI: 10.1007/s11032-020-01151-7
|View full text |Cite
|
Sign up to set email alerts
|

Population genomic and genome-wide association analysis of lignin content in a global collection of 206 forage sorghum accessions

Abstract: Forage sorghum (Sorghum bicolor (L.) Moench) is a wildly cultivated C4 cereal crop in many geographical regions and differs among germplasms in a number of important physiological traits. Lignin is a complex heteropolymer found in plant cell walls that adversely affects economic and environmental benefits of the crop. To understand the genetic basis, we resequenced the genomes of 206 sorghum accessions collected around the globe and identified 14,570,430 SNPs and 1,967,033 indels. Based on the SNP markers, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…More recently, a GWAS of 206 forage sorghum accessions further identified 9 QTLs for lignin content, covering 184 genes. Importantly, 13 of 184 sorghum lignin-related loci were found to have high collinearity with previously reported gene families in other crops (Niu et al 2020 ). These studies would facilitate future genetic breeding of sorghum as bioenergy and forage.…”
Section: Genomic Research In Sorghumsupporting
confidence: 62%
“…More recently, a GWAS of 206 forage sorghum accessions further identified 9 QTLs for lignin content, covering 184 genes. Importantly, 13 of 184 sorghum lignin-related loci were found to have high collinearity with previously reported gene families in other crops (Niu et al 2020 ). These studies would facilitate future genetic breeding of sorghum as bioenergy and forage.…”
Section: Genomic Research In Sorghumsupporting
confidence: 62%
“…QTL mapping for fodder quality traits has not been reported so far. The closest study reported is the association study performed in sorghum for 5 fodder quality traits by identifying 42 SNPs ( Li et al, 2018 ) and population genomic study performed for lignin content in forage sorghum ( Niu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the greater yield potential per unit area of structural carbohydrates (cellulose and hemicellulose) compared to soluble sugars, the first one is expected to allow higher ethanol yield per unit area. Jointly with the definition of the target ideotypes, optimized genetic gains will also depend on a better understanding of the genetic determinism of biochemical (Brenton et al, 2016; Burks et al, 2015; Hennet et al, 2020; Niu et al, 2020) and histological related traits as recently reported in maize (Mazaheri et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Sorghum genotypes with high biomass potentials and suitable to support the development of biomass value chains in temperate (Amaducci et al, 2016) and semi‐arid environments (Oikawa et al, 2015) have already been identified. Sorghum also presents a large phenotypic diversity regarding biomass composition (Brenton et al, 2016; Niu et al, 2020; Trouche et al, 2014) that constitutes a vector of adaptation to diverse biomass value chains.…”
Section: Introductionmentioning
confidence: 99%